PENGARUH LATIHAN BERBALIK DAN MENGOPER BOLA TERHADAP KETERAMPILAN PASSING TIM SSB YAPORA U-15 PEKANBARU - Anwar Ali; Zainur Zainur; Alimandan Alimandan (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: The purpose of this study was to determine the effect of Turning and Passing the ball training on the skills of the U-15 Pekanbaru Yapora SSB Team. The research was conducted at the football field at Jalan Kinibalu Pekanbaru, from October to November 2020. The population which was also the sample in this study was the Yapora U-15 Pekanbaru SSB team, totaling 16 students. Based on the t-test yields a t count of 9,473 with a ttable of 1.753 it is accepted, at the alpha level (0.05. It can be concluded that there is an effect of Turning Training and Passing the Ball on the Skills of Passing the SSB Yapora U-15 Pekanbaru Team. The initial and final tests on 16 people were sampled.Based on the above results, it can be concluded that the Effect of Turning and Passing the Ball Training on the Skills of the Yapora U-15 Pekanbaru SSB Team This shows that turning and passing exercises can be used to improve skills. passing.Key Words: Turning Exercise, Passing the Ball, Passing Skills.